IL-1β Inhibition in Cardiovascular Complications Associated to Diabetes Mellitus - Peiró, Concepción; Lorenzo, Óscar; Carraro, Raffaele; Sánchez-Ferrer, Carlos F. (Frontiers in Pharmacology, 2017)
Diabetes mellitus (DM) is a chronic disease that affects nowadays millions of people worldwide. In adults, type 2 diabetes mellitus (T2DM) accounts for the majority of all diagnosed cases of diabetes. The course of the T2DM is characterized by insulin resistance and a progressive loss of ß-cell mass. DM is associated with a number of related complications, among which cardiovascular complications and atherosclerosis are the main cause of morbidity and mortality in patients suffering from the disease. DM is acknowledged as a low-grade chronic inflammatory state characterized by the over-secretion of pro-inflammatory cytokines, including interleukin (IL)-1ß, which reinforce inflammatory signals thus contributing to the development of complications. In this context, the pharmacological approaches to treat diabetes should not only correct hyperglycaemia, but also attenuate inflammation and prevent the development of metabolic and cardiovascular complications. Over the last years, novel biological drugs have been developed to antagonize the pathophysiological actions of IL-1ß. The drugs currently used in clinical practice are anakinra, a recombinant form of the naturally occurring IL-1 receptor antagonist, the soluble decoy receptor rilonacept and the monoclonal antibodies canakinumab and gevokizumab. This review will summarize the main experimental and clinical findings obtained with pharmacological IL-1ß inhibitors in the context of the cardiovascular complications of DM, and discuss the perspectives of IL-ß inhibitors as novel therapeutic tools for treating these patients.